IMPACT OF EDUCATION TO HEAD OF HOUSEHOLD IN INDONESIA - Maudytia Rismalasari Prabowo; Dominicus Savio Priyarsono; Mutiara Probokawuryan (AFEBI Economic and Finance Review, 2018)
Poverty is one of the most crucial problems in Indonesia which is the fifth city in South-East Asia, have a poverty line around 11.2% in 2014 (BPS 2016). Moreover, poverty in Indonesia has decreased slowly from 2000 (19.1%) until 2016 (10.9%) (Smeru, 2015). It means poverty in Indonesia should be accelerated the decline. One of the things that can reduce poverty is education (Gounder and Xing 2012). Education has a relationship with household consumption per capita. That means, the higher the education of household head, the higher the consumption per capita that household get. The aim of this study is to analyze the impact of education on poverty as measured by household's consumption in West Indonesia in 2014. This study uses Two-Stage Least Square (2SLS) methods with cross-section data and obtained from IFLS (Indonesia Family Life Survey). The result shows that there is a relationship between education and other independent variables on poverty. The independent variables that significantly affect poverty are age, age squared, gender, and marital status. The implication of this study is education can increase the number of consumption per capita so that the living standard will increase and poverty will decrease.JEL Classification: I20, I21, I25Keywords: consumption per capita, cross section, education, Two Stage Least Square, poverty.